2021
DOI: 10.3389/fendo.2020.583229
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of VDBP and 1,25(OH)2D3 on the Viability and Apoptosis of Rheumatoid Arthritis Synovial Fibroblasts

Abstract: AimThis study is to investigate the additive effect of Vitamin D-binding protein (VDBP) and 1,25(OH)2D3 on the viability and apoptosis of synovial cells from patients with rheumatoid arthritis (RA).MethodsSynovial tissues and synovial fluid of patients with RA and osteoarthritis (OA) were collected. The expression of VDBP was analyzed with immunohistochemistry and ELISA. CCK-8 assay was applied to detect cell viability. Flow cytometry was used to analyze cell cycle and apoptosis.ResultsImmunohistochemical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…In the current study, vitamin D binding protein levels were significantly lower in arthritis patients without supplementation (1.26±0.12 ng/ml) compared to those with supplementation (0.75±0.15 ng/ml) and healthy controls (0.23±0.14 ng/ml), (p<0.00). In agreement with our findings, Zhang et al 39 demonstrated that the levels of total vitamin D binding protein were notably lower in rheumatoid arthritis patients compared to control persons and when they with a combination of 1,25(OH)2D3, they observed a slight increase of in vitamin D binding protein. In addition, it is reported that the expression of VDBP in RA patients was lower than that of OA patients.…”
Section: Gendersupporting
confidence: 93%
“…In the current study, vitamin D binding protein levels were significantly lower in arthritis patients without supplementation (1.26±0.12 ng/ml) compared to those with supplementation (0.75±0.15 ng/ml) and healthy controls (0.23±0.14 ng/ml), (p<0.00). In agreement with our findings, Zhang et al 39 demonstrated that the levels of total vitamin D binding protein were notably lower in rheumatoid arthritis patients compared to control persons and when they with a combination of 1,25(OH)2D3, they observed a slight increase of in vitamin D binding protein. In addition, it is reported that the expression of VDBP in RA patients was lower than that of OA patients.…”
Section: Gendersupporting
confidence: 93%